2013
DOI: 10.1161/circoutcomes.111.000071
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Tolerability and Harms of Individual Statins

Abstract: Background-Our objective was to estimate the comparative harms of individual statins using both placebo-controlled and active-comparator trials. Methods and Results-We systematically reviewed randomized trials evaluating different statins in participants with and without cardiovascular disease. We performed random-effects pairwise and network meta-analyses to quantify the relative harms of individual statins. We included 55 two-armed placebo-controlled and 80 two-or multiarmed active-comparator trials includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
106
0
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 247 publications
(115 citation statements)
references
References 48 publications
3
106
0
6
Order By: Relevance
“…However, they are not supported by the randomized controlled trial evidence: in particular, statin therapy has been found to be no less well tolerated than placebo (see below and webtable). 52,62,[236][237][238][239] As is discussed above, the potential biases inherent in studies without both randomly assigned control groups and blinded ascertainment of outcomes limit their ability to demonstrate causal associations (except for large effects on rare outcomes). This is particularly the case for symptomatic adverse events that are attributed to statin use, especially if such reports have been prompted by guidance from clinicians to their patients or from patient information leaflets and other sources.…”
Section: Other Adverse Events That Have Been Attributed To Statin Thementioning
confidence: 99%
“…However, they are not supported by the randomized controlled trial evidence: in particular, statin therapy has been found to be no less well tolerated than placebo (see below and webtable). 52,62,[236][237][238][239] As is discussed above, the potential biases inherent in studies without both randomly assigned control groups and blinded ascertainment of outcomes limit their ability to demonstrate causal associations (except for large effects on rare outcomes). This is particularly the case for symptomatic adverse events that are attributed to statin use, especially if such reports have been prompted by guidance from clinicians to their patients or from patient information leaflets and other sources.…”
Section: Other Adverse Events That Have Been Attributed To Statin Thementioning
confidence: 99%
“…However, the potential side effects of pyrrolidine-2 deter its use in vivo. One of the best tolerated statins is simvastatin [91]. Statins were tested in some CNS diseases and were suggested as supplemental anticancer agents [92,93].…”
Section: Discussionmentioning
confidence: 99%
“…Third, we used a sensitive search strategy to identify RCTs of statins, irrespective of reported outcomes, between 2008 and December 2012. Finally, we reviewed the full text of all studies included in a recent large network meta-analysis of statins (and their adverse effects), 26 and perused the reference lists of RCTs identified through our other approaches.…”
Section: Data Sources and Searchesmentioning
confidence: 99%